Foodborne outbreak after a village festival — Kulon Progo District, Indonesia, 2019 - Laksono, Bima Adi (BKM Public Health and Community Medicine, 2021)
Background : On November 16, 2019, Pengasih 1 Public Health Center (PHC) reported three cases of suspected foodborne outbreak after a village festival in Paingan Village, Pengasih Kulon Progo. Investigation was done to ensure outbreak, identify the risk factors and prevention measure. Methods : The design of this study used Case Control 1:1, a sample taken from a population at risk of 109 respondents, the instrument used was an interview with an epidemiological investigation form. Results : of the 300 Rice boxes served, 109 people were successfully interviewed. There were 63 cases (AR=57.8%), with the main symptoms of nausea, vomiting, and dizziness. The incubation period is 4 - 31 hours. Of all the types of food served, Kerik meat is significantly associated with food poisoning (OR = 9.78 95% CI = 2.6-25.37). Meat is cooked 12 hours before serving and stored at room temperature, meat dishes are cooked by some people. Meat samples, positive laboratory results contain Escherchia Coli. Conclusion : Food poisoning outbreak on November 16, 2019 after consuming kerik meat contaminated with Escherchia Coli. Based on the results of epidemiological studies and laboratory examinations on kerik meat samples, the causative agent of food poisoning is Escherchia Coli. Recommendations by conducting health promotion related to food sanitation hygiene because Escherchia Coli enters through the mouth.